Differentiation in TCM patterns of chronic obstructive pulmonary disease by comprehensive metabolomic and lipidomic characterization - Li, Jiansheng; Liu, Xinguang; Shi, Yanmin; Xie, Yang; Yang, Jianya; Du, Yan; Zhang, Ang; Wu, Jinyan (Frontiers in Immunology, 2023)
Introduction: Chronic obstructive pulmonary disease (COPD) is a complex disease involved with inflammatory, cell senescence and autoimmune. Dialectical treatment for COPD by traditional Chinese medicine (TCM) shows the advantages in less side-effects and more effective suppressing inflammation and improve immune function. However, the biological base of TCM patterns differentiation in COPD is remain unclear. Methods: Liquid Chromatography-Quadrupole-Orbitrap mass spectrometry (LC-Q-Orbitrap MS/MS) based metabolomics and lipidomics were used to analyze the serum samples from COPD patients of three TCM patterns in Lung Qi Deficiency (n=65), Lung-Kidney Qi Deficiency (n=54), Lung-Spleen Qi Deficiency (n=52) and healthy subjects (n=41). Three cross-comparisons were performed to characterize metabolic marker for different TCM patterns of COPD vs health subjects. Results: We identified 28, 8 and 16 metabolites with differential abundance between three TCM patterns of COPD vs health subjects, respectively, the biomarkers included cortisol, hypoxanthine, fatty acids, alkyl-/alkenyl-substituted phosphatidylethanolamine and phosphatidylcholine, etc. Three panels of metabolic biomarkers specific to above three TCM patterns yielded areas under the receiver operating characteristic curve of 0.992, 0.881 and 0.928, respectively, with sensitivity of 97.1%, 88.6% and 91.4%, respectively, and specificity of 96.4%, 81.8% and 83.9%, respectively. Discussion: Combining metabolomics and lipidomics can more comprehensively and accurately trace the metabolic markers. Meanwhile, the differences in metabolism were proved underlie different TCM patterns of COPD, which provided evidences to understand the biological basis of dialectical treatment, and can also serve as biomarkers for more accurate diagnosis.